Molecular identification of a cyclodextrin glycosyltransferase-producinmicroorganism and phylogenetic assessment of enzymatic activities - Caminata Landriel, Soledad (2018)
Cyclodextrin glycosyltransferases (CGTases) are important enzymes in the biotechnology field because they catalyze starch conversion into cyclodextrins and linear oligosaccharides, which are used in food, pharmaceutical and cosmetic industries. The CGTases are classified according to their product specificity in α-, β-, α/β-and γ-CGTases. As molecular markers are the preferred tool for bacterial identification, we employed six molecular markers (16S rRNA, dnaK, gyrB, recA, rpoB and tufA) to test the identification of a CGTase-producing bacterial strain (DF 9R) in a phylogenetic context. In addition, we assessed the phylogenetic relationship of CGTases along bacterial evolution. The results obtained here allowed us to identify the strain DF 9R as Paenibacillus barengoltzii, and to unveil a complex origin for CGTase types during archaeal and bacterial evolution. We postulate that the α-CGTase activity represents the ancestral type, and that the γ-activity may have derived from β-CGTases.